Social Construction of Visually Impaired Students About The Urgency of Arabic Language Education - Hikmah, Nurul; Herawati, Erna; Fauzi, Moch. Sony; Hakim, Luthfi (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2025)
This research aims to understand the social construction of visually impaired students regarding the urgency of Arabic language education at the State Islamic University (UIN) Sunan Kalijaga Yogyakarta. Arabic plays an essential role in Islamic academic fields; however, accessibility for visually impaired students in learning the language remains challenging. Using a qualitative approach, this case study explores the experiences, challenges, and perceptions of visually impaired students in relation to Arabic language learning. Data were collected through in-depth interviews with several visually impaired students and the head and staff of the Disability Services Center (PLD) at UIN Sunan Kalijaga. The findings reveal that visually impaired students have a strong understanding of the urgency of Arabic, both for academic purposes and for enhancing future career opportunities. However, they also voiced various barriers, including limited support facilities and incompatible technology with their needs. This study is expected to provide insights for developing more inclusive policies in Arabic language education for visually impaired students in Islamic higher education settings.